Detecting sub-second changes in brain activation patterns during interictal epileptic spike using simultaneous EEG-fMRI. Issue 2 (February 2018) - Bagarinao, Epifanio; Maesawa, Satoshi; Ito, Yuji; Usui, Naotaka; Natsume, Jun; Watanabe, Hirohisa; Hoshiyama, Minoru; Wakabayashi, Toshihiko; Sobue, Gen; Naganawa, Shinji; Isoda, Haruo
Highlights: We proposed a method to construct dynamic fMRI activation maps with milliseconds temporal resolution. Rapidly changing activation patterns involving the epileptic focus and other regions were identified. Summary maps (SSWAS maps) enabled the detection of the epileptic foci where event-related methods failed. Abstract: Objective: Epileptic spikes are associated with rapidly changing brain activation involving the epileptic foci and other brain regions in the "epileptic network". We aim to resolve these activation changes using simultaneous electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) recordings. Methods: Simultaneous EEG-fMRI recordings from 9 patients with epilepsy were used in the analysis. Our method employed the whole scalp EEG data to generate regressors for the analysis of fMRI data using the general linear model. Results: We were able to resolve, with milliseconds temporal resolution, changes in activation patterns involving suspected epileptic foci and other brain regions in the epileptic network during spike and slow wave. Using summary maps (called SSWAS maps) which show the activation frequency of voxels, we found that suspected epileptic foci tend to be significantly active during this interval. SSWAS maps also enabled the detection of the epileptic foci in 4 of 5 patients where the conventional event-timing-based analysis failed to identify. Conclusion: These findings demonstrated the efficacy of the method and the potential application of SSWAS maps to identify epileptic foci. Significance: The method could help resolve activation changes during epileptic spike and could provide insights into the underlying pathophysiology of these changes.